An Improvement in Boundary Treatment of Solid Boundary Using ISPH Approach - Idris, Nur’Ain; Asai, Mitsuteru; Mohd Noh, Hamidun (semarak ilmu, 2023)
Incompressible Smoothed Particle Hydrodynamic (ISPH), one of the particle methods, is frequently employed to address a variety of challenging physical issues, such as those involving free surface flow. For measuring the precise and reliable pressure close to the boundary, the study of boundary treatment has lately been an active research field in the mesh-free or particle approach. If the solid barrier's appropriate pressure boundary condition is not met, fluid particles may penetrate it. This study proposes a straightforward boundary treatment that can satisfy the non-homogenous Neumann boundary condition on the solid boundary and the Dirichlet condition on the water surface. The main idea behind our suggested approach is that by solving a modified pressure Poisson equation, these boundary conditions are automatically satisfied. This technique can be improved such that it can be applied to any shape having a concaveconvex boundary in addition to basic solid boundaries. The suggested method was tested using the hydrostatic case, followed by a numerical analysis validated using a 3D dam break flow with an opening gate and a Stanford rabbit demonstration. The outcome of the numerical modelling simulation was then contrasted with the findings of the theoretical and experimental studies. The obtained findings support the suggested technique by providing a good tendency and similarity output that enhances the boundary treatment on solid boundaries.